ANALYSIS OF GENE TARGETING EVENTS IN BUCKWHEAT (Fagopyrum esculentum) TRANSFORMED b THE MUTANT STRAINS OF Agrobacterium tumefaciens THAT HAVE DEFICIENCY IN T-??DNA INTEGRATION STEP INTO PLANT GENOME - Mineo Kojima; Putu Suparthana; Tsutomu Shimizu; Masahiro Nogawa (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University in cooperation with Asia-Oceania Bioscience and Biotechnology Consortium (AOBBC), 2014)
Gene targeting events were analyzed in buckwheat (Fagopyrum esculentum, var. Shinano No. 1) that werein planta transformed (T1) by the three strains of Agrobacterium tumefaciens harboring a gene targetingvector for an endogenous gene (acc.no.AB327276); M-??1 mutant (abvA::Tn5) and M-??31 mutant (virA::Tn5)strains, both of which are capable of transferring its T-??DNA into nucleus of host plant cell, but have adeficiency in T-??DNA integration step into chromosome and LBA4404 strain, being a commonly usedstrain. The results of both phenotype examination and Southern blot analysis implied that a targetingconstruct(s) was integrated into a different locus (loci) each depending on the strain of A. tumefaciens usedfor transformation. Both 5’-??end and 3’-??end flanking DNA segments that were expected from preciseinsertion of targeting construct into the endogenous U-??gene locus were obtained by PCR with 3 (23%)transformants out of the randomly selected 13 transformants by M-??1 mutant strain, while only 3’-??endflanking DNA segment was obtained with 3(21%) transformants out of 14 transformants by M-??31 strain.Taken together, the results suggested the potential of usage of a mutant strain of A. tumefaciens for genetargeting which has a deficiency in T-??DNA integration step into plant genome.